Idea agent : leadership that liberates creativity and accelerates innovation - Echeverría, Lina M. (American Management Association, 2012)
The will to manage, the guts to decide, the wisdom to guide, and the passion to make innovation happen.
Includes index.
Keywords: Creative ability in business.; Self-actualization (Psychology); Leadership.; elektronické knihy; electronic books